Malaysian teachers’ perceptions towards emergency remote teaching (ERT): An analysis based on school level and subjects taught - Daron Benjamin Loo (Universiti Kebangsaan Malaysia, 2024)
This study analyses teachers’ perceptions towards emergency remote teaching (ERT), based on the level and subject area taught. Perception data was collected through an online anonymous survey, which contained 30 survey items on a 5-point Likert scale. There were 97 participants who completed the survey. The data was analysed using descriptive statistics. The main fi ndings include teachers of all levels and subjects having a clear understanding of students’ current learning situation, yet there were some uncertainty regarding the planning and implementation of online teaching and learning, especially among primary-level teachers and teachers of science subjects. Another major fi nding was the agreement among teachers regarding the documentation of teaching experiences and sharing these experiences with others. Based on these fi ndings, it can be concluded that while there is a perception that ERT is diff erent from regular online teaching, there remains challenges in the implementation of online classes. A potential way to mitigate these challenges may be to encourage teachers to share, so as to inspire each other to identify potential and feasible ways to teach.